2016
DOI: 10.1016/j.mgene.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of apolipoprotein E and aneurysmal subarachnoid haemorrhage: A meta-analysis

Abstract: Subarachnoid haemorrhage (SAH) is characterised by bleeding in the subarachnoid space in the brain. There are various polymorphisms in genes which are associated with this disease. We performed a systematic meta- analysis to investigate the relationship of APOE polymorphism on aSAH. A comprehensive literature search was done in the Pubmed database, Science Direct, Cochrane library and Google Scholar. The OR and 95% CI were evaluated for the gene and aSAH association using fixed and random effect models. Public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In our present study, we found the distribution of ε2/ε3 genotype in aSAH was higher than the healthy controls, and allele frequencies of ApoE ε2 in aSAH was also higher than controls. Latter, using the multivariate logistic regression analysis, we found that ApoE ε2 allele was significantly increased compared to ε3 in aSAH (OR = 2.083, 95% CI = 1.045-4.153, P = 0.037), suggesting that ε2 allele is a risk factor for aSAH, which was consistent with the result of the previous meta-analysis [ 24 ] and the study of Liu et al [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our present study, we found the distribution of ε2/ε3 genotype in aSAH was higher than the healthy controls, and allele frequencies of ApoE ε2 in aSAH was also higher than controls. Latter, using the multivariate logistic regression analysis, we found that ApoE ε2 allele was significantly increased compared to ε3 in aSAH (OR = 2.083, 95% CI = 1.045-4.153, P = 0.037), suggesting that ε2 allele is a risk factor for aSAH, which was consistent with the result of the previous meta-analysis [ 24 ] and the study of Liu et al [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…A recently meta-analysis of 9 studies, which was mainly including Caucasian and Asian population, have showed that there was a significant association between APOE genotype and aSAH, and ε2 allele was a risk factor for aSAH [ 24 ]. In our present study, we found the distribution of ε2/ε3 genotype in aSAH was higher than the healthy controls, and allele frequencies of ApoE ε2 in aSAH was also higher than controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of nine case control studies found that in the Asian population, ε2/ε2 vs. ε3/ε3, ε2/ε3 vs. ε3/ε3, ε2 vs. ε3 and ε2 allele frequency were associated with the risk of aSAH. However, the study concluded that only the ε2/ε2 vs. ε3/ε3 genetic model was associated with the risk of aSAH in the Caucasian population [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ε4 allele is associated with unfavorable outcomes after traumatic brain injury [ 17 , 18 ] and aSAH in the Chinese and Italian population [ 19 , 20 ]. We performed a meta-analysis that suggested that there is significant association with the risk of aSAH in ε2/ε2 vs. ε3/ε3, ε2/ ε3 vs. ε3/ε3 and ε2 vs. ε3 genetic models and ε2 allele frequency [ 21 ].…”
Section: Introductionmentioning
confidence: 99%